Linking Terpene Synthases to Sesquiterpene Metabolism in Grapevine Flowers - Smit, Samuel Jacobus; Vivier, Melané Alethea; Young, Philip Richard (Frontiers in Plant Science, 2019)
Grapevine (Vitis vinifera L.) terpene synthases (VviTPS) are responsible for the biosynthesis of terpenic volatiles. Volatile profiling of nine commercial wine cultivars showed unique cultivar-specific variation in volatile terpenes emitted from grapevine flowers. The flower chemotypes of three divergent cultivars, Muscat of Alexandria, Sauvignon Blanc and Shiraz were subsequently investigated at two flower development stages (EL-18 and -26). The cultivars displayed unique flower sesquiterpene compositions that changed during flower organogenesis and the profiles were dominated by either (E)-β-farnesene, (E, E)-α-farnesene or (+)-valencene. In silico remapping of microarray probes to VviTPS gene models allowed for a meta-analysis of VviTPS expression patterns in the grape gene atlas to identify genes that could regulate terpene biosynthesis in flowers. Selected sesquiterpene synthase genes were isolated and functionally characterised in three cultivars. Genotypic differences that could be linked to the function of a targeted gene model resulted in the isolation of a novel and cultivar-specific single product sesquiterpene synthase from Muscat of Alexandria flowers (VvivMATPS10), synthesising (E)-β-farnesene as its major volatile. Furthermore, we identified structural variations (SNPs, InDels, splice variations) in the characterised VviTPS genes that potentially impact enzyme function and/or volatile sesquiterpene production in a cultivar-specific manner.